2020
DOI: 10.1089/ham.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Medical Problems in Himalayan Porters

Abstract: Porters have accompanied trekkers and climbers to high altitude since the earliest expeditions in the Himalayas. As the existing body of knowledge on high altitude medicine expands, the focus remains on trekkers or climbers and published literature on medical problems in the large porter population remains sparse. It is well known that porters working at high altitude in the Nepal Himalayas are often lowland dwellers and are as prone to high altitude illnesses like acute mountain sickness (AMS), high altitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, the focus has been posed to highland dwellers and to lowland trekkers and climbers. Therefore, there is a lack of evidence on those who are generally lowland dwellers working at high altitudes, such as porters, who logistically support expeditions and are prone to high altitude illnesses [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the focus has been posed to highland dwellers and to lowland trekkers and climbers. Therefore, there is a lack of evidence on those who are generally lowland dwellers working at high altitudes, such as porters, who logistically support expeditions and are prone to high altitude illnesses [7].…”
Section: Introductionmentioning
confidence: 99%
“…The reality that porters are also in danger of risk of AMS is very significant for trekking cohorts, businesses, and tourists to identify as there is frequently a fictitious presumption that porters working at lofty elevation locations all come from lofty elevations and are, consequently, comparatively resistant to AMS. The research presented here found that it is vital to recognize that this is not the situation and awareness has to be devoted to the porters touring with any given trekking or mountaineering group (Dawadi, Basnyat & Adhikari, 2020;Bellows, 2014). Indeed, it is quite difficult to acquire statistics concerning the deaths of porters/Sherpas when climbing or trekking to high altitudes.…”
Section: Literature Reviewmentioning
confidence: 96%
“…According to Dawadi, Basnyat and Adhikari (2020), all Sherpa porters are not from lofty elevation locations. In effect, a considerable percentage of them are from diverse ethnic origins and inhabit low elevations and only journey to lofty elevation locations for employment (Barott, 2018;Koirala et al, 2018;Newcomb et al, 2011;Malville et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%